Meningkatkan Hasil Belajar PAK SMP VII Santo Antonius Bangun Mulia dengan Model Core - Siregar, Mariana; Sihotang, Din Oloan (Vocat : Jurnal Pendidikan Katolik, 2024)
Based on this study, the learning outcomes of Catholic Religious Education (PAK) for seventh-grade students at SMP Santo Antonius Bangun Mulia Medan will be evaluated for its effectiveness using the CORE Learning Model. Over two research cycles, 26 students participated in this action research using the Classroom Action Research (CAR) method. In addition to tracking the learning process, data were collected through pre- and post-tests. Empirical evidence shows that the CORE Learning Model can significantly improve student learning outcomes. Cycle I obtained an average post-test score of 88.2, while Cycle II obtained an average post-test score of 96.3. Compared to the previous average pre-test scores of 63.3 and 89, these figures indicate progress. These findings are consistent with previous research showing the effectiveness of the CORE Learning Model in increasing student engagement and academic performance. The conclusion of this study is that the CORE Learning Model can serve as a tool to enhance student learning outcomes in PAK and promote the development of more engaging and effective teaching strategies. This research aims to assist academics and educators in developing innovative and effective teaching methods.